(untitled) (Revista Científica Integrada, 2023)
Objective: To identify the profile of elderly people with non-transmissible chronic conditions assisted by Primary Health Care. Methods: This is a cross-sectional study, based on the STROBE checklist. Data collection took place in November 2022 with elderly people monitored by the Family Health Strategy. Elderly people who had a diagnosis of at least one chronic condition verified in the medical records of two-Family Health Centers were selected. The sample was for convenience, consisting of 50 elderlies. Data collection took place from interviews through a semi-structured script with closed questions with sociodemographic and health data. Data were processed using SPSS software and analyzed using descriptive and inferential statistics. Results: There was a prevalence of females (70%), aged between 60 and 64 years (30%), married (62%), incomplete primary education (72%), living with a partner/spouse and/or children (62%); hypertensive (62%) and used four or more medications (30%); in addition, it was identified that the age group was statistically associated with comorbidities in this population. Conclusion: Chronic conditions were more present in young, married elderly people with a low level of education. Hypertension was the most prevalent disease, which represents a significant impact on the Unified Health System, especially if social determinants of health and related risk factors are considered.